Erratum to: Bridging the gap between economic modelling and simulation: a simple dynamic aggregate demand-aggregate supply model with matlab (Journal of Applied Mathematics (2018) 2018 (3193068) DOI: 10.1155/2018/3193068) - Gaspar, José M. (2018)
In the article titled "Bridging the Gap between Economic Modelling and Simulation: A Simple Dynamic Aggregate Demand-Aggregate Supply Model with Matlab" [1], an incomplete version of the SupplementaryMaterials was published. Also, there was a typographical error in the numerical evaluation section, where the word "supplemantary" should be corrected to "supplementary." This occurred due to production errors. The complete updated version of the Supplementary Materials is available here. Supplementary Materials The Matlab code is embedded in a single function (ADASdynamic. m). Add the ".m" file to the working Matlab path/directory. Open Matlab and run the name of the file in the command window (ADASdynamic). The programme asks the user to introduce values for the parameters described throughout the paper, including the initial time and final time. It then produces three figures: one is for the solution y(t), another is for both πe(t) and π(t), and the last one shows the phase diagram portraying the transition dynamics. The programme will then ask the user to implement either monetary, fiscal, supply side shocks, or any possible combination of shocks, by introducing new values for the money growth rate, public spending, tax rate, and level of natural output. This will produce three new graphs, with the same information as described previously, but compared to the initial situation. Therefore, the figures shown after implementing shocks will portray the global transition dynamics towards the new equilibrium. Along these processes, the output for the relevant steady-state levels and their qualitative properties are shown in Matlab's command window, along with the parameter values. See Appendix B for an example of how the output is displayed inMatlab's command window. (Supplementary Materials).